ANALISIS JUAL BELI TOKEK MENURUT PERSPEKTIF HUKUM ISLAM - Imam Fawaid (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2021)
Buying and selling in Islam must be carrieda out with the provisions of syara', which must meet the pillars and conditions. Today the sale of geckos is not a perpetual thing. It can even be used as a very profitable business area. This makes the breeders compete to hunt and raise geckos. In addition, breeders need a long time and hard work to meet consumer demand. One of them is to place the gecko in a quiet place and make crickets or dried shrimp as food. In this case the marketing, consumers usually come directly to the breeder and choose which gecko they want to buy. Most consumers prefer geckos that are large (± 3 ounces) and ready to use. From there arose the problem of how the perspective of Islamic law in dealing with the sale and purchase of geckos emerged. The type of research used is field research with qualitative descriptive research methods. The results of the research on the sale and purchase of geckos, there are several opinions from the madhhab priests, including Imam Syafi'I who argues that the sale and purchase of geckos is unlawful, and Imam Malik argues that buying and selling geckos is legal and according to Imam Hanafi's opinion it allows the buying and selling of geckos on condition that there are the benefits. And Islam itself allows consuming geckos as long as the gecko is needed as a medicine for human survival and selling and buying it is also legal.